Colo-articular fistula following a Girdlestone resection arthroplasty - El-Daly, Ibraheim (Oxford University Press, 2014)
Colo-articular fistulas are rare complications that are usually associated with inflammatory, infective or malignant bowel disease. We report the case of a 44-year-old male who was found to have a colo-articular fistula intra-operatively during the washout of a septic hip joint. The patient had no pre-existing bowel disease, but was an intravenous drug user, who had previously undergone a Girdlestone procedure for osteomyelitis of the proximal femur. The patient was managed through a multi-disciplinary team approach with subsequent debridement and formation of a transverse loop colostomy to control the faeculent fistulous discharge.